Empirically validated theoretical analysis of visual-spatial perception under change of nervous system arousal - Purohit, Pratik; Dutta, Prasun; Roy, Prasun K. (Frontiers in Computational Neuroscience, 2023)
INTRODUCTION: Visual-spatial perception is a process for extracting the spatial relationship between objects in the environment. The changes in visual-spatial perception due to factors such as the activity of the sympathetic-nervous system (hyperactivation) or parasympathetic-nervous system (hypoactivation) can affect the internal representation of the external visual-spatial world. We formulated a quantitative model of the modulation of visual-perceptual space under action by hyperactivation or hypoactivation-inducing neuromodulating agents and showed a Hill equation based relationship between neuromodulator agent concentration and alteration of visual-spatial perception utilizing the metric tensor to quantify the visual space. . METHODS: We computed the dynamics of the psilocybin (hyperactivation-inducing agent) and chlorpromazine (hypoactivation-inducing agent) in brain tissue. Then, we validated our quantitative model by analyzing the findings of different independent behavioral studies where subjects were assessed for alterations in visual-spatial perception under the action of psilocybin and under chlorpromazine. To validate the neuronal correlates, we simulated the effect of the neuromodulating agent on the computational model of the grid-cell network, and also performed diffusion-MRI-based tractography to find the neural tracts between the cortical areas involved V2 and entorhinal cortex. . RESULTS We applied our computational model to an experiment (where perceptual alterations were measured after under-psilocybin) and found that for "n" (Hill-coefficient)=14.8 and "k"=1.39, theoretical prediction followed experimental observations very well (χ2 test robustly satisfied, p>0.99). We predicted the outcome of another psilocybin-based experiment using these values ("n"=14.8 and "k"=1.39), whereby our prediction and experimental outcomes were well corroborated. Furthermore, we found that also under hypoactivation (under-chlorpromazine), modulation of visual-spatial perception follows our model. Moreover, we found neural tracts between the area V2 and entorhinal-cortex, thus providing a possible brain network responsible for encoding visual-spatial input. Thence, we simulated the altered grid-cell network activity, which was also found to follow the Hill equation. . CONCLUSION: We developed a computational model of visuospatial perceptual alterations under altered neural sympathetic/parasympathetic tone. We validated our model using analysis of behavioral studies, neuroimaging analysis, and neurocomputational model. Our quantitative approach may be probed as a potential behavioral screening and monitoring methodology in neuropsychology to analyze perceptual misjudgment and mishaps by highly-stressed workers.